Parametric Analysis and Optimization of Sinker-EDM Process for High Tensile Strength Steel Using Response Surface Methodology - Rohman; Sukarman, Sukarman; Khoirudin, Khoirudin; Taufik Ulhakim, Muhamad; Mulyadi, Dodi; Amir, Amir; Abdulah, Amri (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2024)
This investigation focuses on optimizing the sinker electrical discharge machining (sinker-EDM) process parameters for high tensile strength steel (HTSS), specifically SKD-11, utilizing Box-Behnken Response Surface Methodology (BB-RSM). Sinker-EDM is a commonly used technique in manufacturing moulds, dies, and components for sectors like automotive and aerospace. This process eliminates direct contact between the electrode and the workpiece. However, its low material removal rate (MRR) constrains productivity. This research endeavours to enhance MRR by employing rectangular graphite electrodes. The Box-Behnken Response Surface Methodology (BB-RSM) was utilized to evaluate the effects of pulse current, spark-on time, and gap voltage on MRR. The optimal MRR of 45.49 mm³/min was attained at a pulse current of 16 A, spark-on time of 400 µs, and gap voltage of 45 V. ANOVA revealed that pulse current and spark-on time significantly influenced MRR. In contrast, gap voltage had an insignificant impact. Interaction and surface plot analyses confirmed that high pulse current and extended spark-on time resulted in the maximum MRR. These findings provide valuable insights for optimizing the sinker-EDM process for SHTSS, contributing to enhanced productivity and efficiency in manufacturing.